Commentary: Indefensible Methods of Handling Missing Data in Clinical Trials. (18th October 2013) - Arndt, Stephan
<x xml:space="preserve">Abstract</x> Background Literature continues to appear using inappropriate statistical methods when dealing with missing data in treatment trials. I regularly see last observation carried forward, assumed worst‐case scenario, or some other static imputation method still being submitted and published in journals. Methods We briefly cover a few reasons why the use of more modern and defensible methods may not have completely saturated the literature. Results While some delay in complete permeation of appropriate methods is understandable, we are currently past the point for reasonable delay. Conclusions Editors and reviewers should demand appropriate statistical methods in published literature.